Association between systemic immune-inflammation index and latent tuberculosis infection: a cross-sectional study - Pang, Ting; Wang, Lei; Zhang, Jie; Duan, Shuhong (Frontiers in Medicine, 2025)
BackgroundThe systemic immune-inflammation index (SII) has been associated with various diseases, but its relationship with latent tuberculosis infection (LTBI) remains unclear. This study aimed to evaluate the association between SII and LTBI in United States adults.MethodsData were obtained from the National Health and Nutrition Examination Survey (NHANES) 1999–2000 and 2011–2012 cycles. LTBI was defined as a positive result on either the QuantiFERON®-TB Gold In-Tube (QFT-GIT) assay or the tuberculin skin test (TST). SII was calculated based on neutrophil, platelet, and lymphocyte counts. All analyses were performed using complex survey design and sampling weights. Multivariable logistic regression models were applied to evaluate the association between SII and LTBI. SII was also analyzed in quartiles to assess trends. Restricted cubic spline (RCS) was employed to explore the potential non-linear associations. Subgroup analyses were conducted to assess whether the association varied across demographic and clinical strata.ResultsA total of 9,489 participants were included, among whom 1,068 were identified with LTBI. Multivariable logistic regression demonstrated that SII was inversely associated with LTBI. For each 100-unit increase in SII, the odds of LTBI decreased by 6% (adjusted OR = 0.94, 95% CI: 0.90–0.97). When analyzed by quartiles, participants in the highest quartile had significantly lower odds of LTBI compared to those in the lowest quartile (adjusted OR = 0.58, 95% CI: 0.41–0.81), with a significant trend across quartiles (P for trend = 0.003). RCS showed a linear relationship between SII/100 and LTBI (P for non-linearity >0.05). The results of further subgroups analysis were consistent, with a significant interaction observed only for HIV status (P for interaction = 0.034).ConclusionSII was inversely associated with LTBI and may serve as a readily accessible marker for LTBI risk stratification. Given its non-specific nature, further longitudinal studies are needed to validate its clinical and public health utility.